Specification of the process of chloride extraction from reinforced concrete based on the inverse task of the diffusion equation - Alsabry, Abdrahman; Zybura, Adam (Zielona Góra: Uniwersytet Zielonogórski)
When the structure of reinforcement is in danger of chloride corrosion it is possible to prevent this disadvantageous phenomenon through exposing the cover to the influence of an electric field. The forces of an electric field considerably reduce chloride ions in pore liquid in concrete, which helps to rebuild a passive layer on the surface of the reinforcement and stops corrosion. The process of removing chlorides can be described with multi-component diffusion equations. However, an essential parameter of these equations, the diffusion coefficient, can be determined on the basis of an inverse task.
Keywords: corrosion; diffusion; inverse task; removing chlorides; extraction